2017
DOI: 10.3390/su9101722
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Financial Performance of Companies in the Energy Sector in Romania

Abstract: Abstract:In the article, we focus on the question of sustainability in the renewable energy sector of Romania. The aim of the current paper is to analyze the financial performance of the companies operating in the field. Our assumption is that the success of the implementation of the energy switch from classic to renewables relies on the businesses operating in this industry. In our article, we have selected the most prominent players in the energy industry, comparing the performance of those that are producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 14 publications
2
48
1
Order By: Relevance
“…Although the quality of a product is an operational measurement, there is a linkage between product quality and the economic performance of firms [29]. Product quality is a direct responsibility of the managers and it is one of the most important reflections of the economic performance of a company [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the quality of a product is an operational measurement, there is a linkage between product quality and the economic performance of firms [29]. Product quality is a direct responsibility of the managers and it is one of the most important reflections of the economic performance of a company [24].…”
Section: Methodsmentioning
confidence: 99%
“…Other types of analysis, such as the Bohl et al study [23], could not be replicated for the Romanian market since there are a few companies operating in the renewable energy sector that are listed on the stock exchange. An overview of the sustainability and financial performance of the companies in the energy sector in Romania [24] has been recently undertaken, so the authors of this paper decided to take a different approach by investigating the economic performance of the companies in this sector. Energy and clean energy have been one of the most widely debated issues in the last years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study by Mervelskemper, Kaltofen, and Stein () found that investors in German sustainability funds do not have to sacrifice financial performance. Other studies focused on the sustainability aspect and its relationship with firm financial performance (Adegbite, Guney, Kwabi, & Tahir, ; Al Abri, Bi, Mullally, & Hodges, ; Amacha & Dastane, ; del Alonso‐Almeida, Bagur‐Femenias, Llach, & Perramon, ; Kim & Lee, ; Maletic, Maletic, Dahlgaard, Dahlgaard‐Park, & Gomišcek, ; Paun, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jung et al [13] proposes a corporate sustainability measure to integrate environmental performance along five dimensions for oil companies. Paun [14] links environmental performance to financial performance for energy companies in Romania. Shvarts et al [15] study the environmental responsibility rating of 19 Russian oil and gas companies based on their performance in 2014.…”
Section: Literature Reviewmentioning
confidence: 99%